Design and Build a Weather Prediction Station For Rice Drying SMIs: Rancang Bangun Stasiun Prediksi Cuaca untuk IKM Pengeringan Beras - Henry, William; Hari, Yulius; Prayitno, Agus (JOINCS (Journal of Informatics, Network, and Computer Science), 2021)
The weather prediction tool is a microcontroller-based automatic weather monitoring tool that can monitor changes in temperature, humidity, air pressure through sensors that have been placed and programmed to detect weather conditions around the monitoring location. This tool is designed to be able to monitor and manage data from anywhere in the area where this tool is placed as long as there is an internet connection. To add flexibility, the sensor data processed on the ESP32 microcontroller will be connected to an access point on the 2.4 GHz wireless network, then the data will be sent to the web server and will be displayed on the website. The focus of making this weather prediction tool is that it is hoped that with this weather prediction tool, factory owners can be assisted in the process of drying the grain, so that the dried grain can be peeled off and can be processed using a grinding machine to be sold to consumers in the form of rice.